Thiamine as a neuroprotective agent after cardiac arrest. (August 2016) - Ikeda, Kohei; Liu, Xiaowen; Kida, Kotaro; Marutani, Eizo; Hirai, Shuichi; Sakaguchi, Masahiro; Andersen, Lars W.; Bagchi, Aranya; Cocchi, Michael N.; Berg, Katherine M.; Ichinose, Fumito; Donnino, Michael W.
Abstract: Aims: Reduction of pyruvate dehydrogenase (PDH) activity in the brain is associated with neurological deficits in animals resuscitated from cardiac arrest. Thiamine is an essential co-factor of PDH. The objective of this study was to examine whether administration of thiamine improves outcomes after cardiac arrest in mice. Secondarily, we aimed to characterize the impact of cardiac arrest on PDH activity in mice and humans. Methods: Animal study : Adult mice were subjected to cardiac arrest whereupon cardiopulmonary resuscitation was performed. Thiamine or vehicle was administered 2 min before resuscitation and daily thereafter. Mortality, neurological outcome, and metabolic markers were evaluated. Human study : In a convenience sample of post-cardiac arrest patients, we measured serial PDH activity from peripheral blood mononuclear cells and compared them to healthy controls. Results: Animal study : Mice treated with thiamine had increased 10-day survival (48% versus 17%, P < 0.01) and improved neurological function when compared to vehicle-treated mice. In addition, thiamine markedly improved histological brain injury compared to vehicle. The beneficial effects of thiamine were accompanied by improved oxygen consumption in mitochondria, restored thiamine pyrophosphate levels, and increased PDH activity in the brain at 10 days. Human study : Post-cardiac arrest patients had lower PDH activity in mononuclear cells than did healthy volunteers (estimated difference: ⿿5.8 O.D./min/mg protein, P < 0.001). Conclusions: The provision of thiamine after cardiac arrest improved neurological outcome and 10-day survival in mice. PDH activity was markedly depressed in post-cardiac arrest patients suggesting that this pathway may represent a therapeutic target.